United in our challenges - should the model used in clinical legal education be reviewed? - Mahomed, S. H. (Faculty of Law, University of the Free State, 2008)
The University of the Witwatersrand Law Clinic has used the in-house real-client model of clinical legal education since 1973. Now, 30 years later, the author reflects on the challenges that this model poses, particularly in light of the evolution of clinical teaching in the 21 '' century. This paper considers various models used in clinical teaching, with particular emphasis on the "real-client" model as used in clinical teaching at the University of the Witwatersrand Law Clinic. Various challenges posed by this model are identified and discussed. In conclusion certain recommendations are put forward on how to deal with these challenges.

Die Universiteit van die Witwatersrand Regskliniek gebruik sedert 1973 die binneshuise ware klient-model in kliniese regsonderrig. Nou, ongeveer 30 jaar later, neem die skryfster hierdie model en die uitdagings wat dit bied onder oe, veral gesien in die lig van evolusie van kliniese onderrig in die 21 ''' eeu. Die artikel oorweeg verskeie modelle wat in kliniese onderrig gebruik word, met besondere klem op die "ware klient"-model soos gebruik in kliniese onderrig by die Universiteit van die Witwatersrand se Regskliniek. Verskeie uitdagings wat die model bied word ge"i"dentifiseer en bespreek. Ten slotte word sekere aanbevelings gemaak oor hoe hierdie uitdagings hanteer kan word.
Keywords: Clinical legal education; Clinical teaching; University of the Witwatersrand Law Clinic; Real-client model; Clinical legal education programmes